AN IMPLICATURE ANALYSIS ON THE MAIN CHARACTER’S UTTERANCES IN CARS 2 MOVIE - Budiono, Nanda (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study describes the implementation of Relevance Theory to convey the implicatures of Mater’s utterances in Cars 2 movie. Mater is the main character of Cars 2 movie whose utterances frequently causes misunderstanding between Mater and other characters in the movie. Other characters in Cars 2movie who misunderstand Mater’s utterances are Lightning McQueen, Francesco Bernoulli, Holley Shiftwell, Finn McMissile, and Mater’s voice-activated computer. In analyzing the implicatures of Mater’s utterances which are misunderstand by other characters in Cars 2 movie, the writer considers the contextual effect of Mater’s utterances toward hearer’s existing assumption. The implicatures of Mater’s utterances can be conveyed from the deduction of its contextual effect.